2018
DOI: 10.1123/ijspp.2017-0112
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Effects of Performance Level and Sex on Sprint Performance in the Biathlon World Cup

Abstract: Biathlon is an Olympic sport combining cross-country skiing with the skating technique and rifle shooting. The sprint (7.5 km for women and 10 km for men) includes two shootings between the three laps of skiing. The aims of the current study are to compare biathletes of different performance-levels and sex on total race time and performance-determining factors of sprint races in the biathlon World Cup. The top 10-performers (G1-10) and results within performance (rate of hits) and penalty time. G21-30 among me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
45
2
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 37 publications
(62 citation statements)
references
References 26 publications
14
45
2
1
Order By: Relevance
“…Furthermore, the correlation between XC skiing and overall performance was clearly larger than the corresponding correlations for the overall shooting component. These main findings extend upon the recent findings by Luchsinger et al (2018) who revealed XC skiing time to be the most important contributor to the overall performance difference between top-10 results and those finishing among 21-30 in both sexes in biathlon World Cup sprint races. In the study by Luchsinger et al (2018), XC time explained ∼60% of the variance in overall performance when averaged over 47 World Cup sprint races.…”
Section: Overall Biathlon Sprint Race Performancesupporting
confidence: 88%
See 4 more Smart Citations
“…Furthermore, the correlation between XC skiing and overall performance was clearly larger than the corresponding correlations for the overall shooting component. These main findings extend upon the recent findings by Luchsinger et al (2018) who revealed XC skiing time to be the most important contributor to the overall performance difference between top-10 results and those finishing among 21-30 in both sexes in biathlon World Cup sprint races. In the study by Luchsinger et al (2018), XC time explained ∼60% of the variance in overall performance when averaged over 47 World Cup sprint races.…”
Section: Overall Biathlon Sprint Race Performancesupporting
confidence: 88%
“…These main findings extend upon the recent findings by Luchsinger et al (2018) who revealed XC skiing time to be the most important contributor to the overall performance difference between top-10 results and those finishing among 21-30 in both sexes in biathlon World Cup sprint races. In the study by Luchsinger et al (2018), XC time explained ∼60% of the variance in overall performance when averaged over 47 World Cup sprint races. The larger influence of XC skiing time found here may be due to different methodologies between the studies, as well as natural variations across competitions (e.g., racecourses with different terrain in the sections prior to shooting and variation in snow and weather conditions).…”
Section: Overall Biathlon Sprint Race Performancesupporting
confidence: 88%
See 3 more Smart Citations